Validation study of the Italian brief version of the multidimensional jealousy scale: Psychometric properties, measurement invariance across gender, and convergent validity - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Girelli, Laura; Cavicchiolo, Elisa; Chirico, Andrea (Frontiers in Psychology, 2022)
The Multidimensional Jealousy Scale (MJS) is among the most internationally used instruments for the assessment of jealousy in its three dimensions: cognitive, emotional and behavioral. This study aimed to replicate the Italian validation process of the shortened MJS in order to confirm its psychometric properties with a large sample of adults (n = 2,928). A 15-item version was retained in its three factor structure. The tool showed good fits with both the CFA (χ2 = 211.827, CFI = 0.969, TLI = 0.959, RMSEA = 0.047, RMSEA 90% CI = .039-.055) and the gender Measurement Invariance. The internal consistency measures were found to be fully satisfactory. Convergent validity was tested by administrating the tool to a further convenient sample (n = 304). Predictive indications with constructs such as avoidance and anxiety referred to attachment in relationships (ECR-R), obsessive jealousy, depressive jealousy, jealousy associated with separation anxiety, paranoid jealousy (QUEGE), basic self-esteem (BSE) and codependency (FSCS) were confirmed. The scale is particularly apt to quickly and efficiently collect information about jealousy in a current relationship. The multidimensional and brief structure makes it particularly suitable for preliminary screening, couple therapy assessment, and research purposes.